The Use of Heuristic Evaluation Method as Usability Analysis and Interface Redesign for JConnect Mobile Application of Bank Jatim: Penggunaan Metode Heuristic evaluation sebagai Analisis Usability dan Redesign Antarmuka pada Aplikasi JConnect Mobile Bank Jatim - Aditama, Rizky Rafi; Eka Prismana, I Gusti Lanang Putra (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2023)
The JConnect Mobile application is a mobile banking service provided by Bank Jatim. This application has been downloaded by more than four hundred users, but the ratings or evaluations given by users are not satisfactory. User responses indicate issues with the usability of the app's interface, which has led to user dissatisfaction and low ratings. User experience and interface design are crucial factors in an application. Therefore, an evaluation is necessary to measure the quality of the JConnect Mobile app. In this study, the System Usability Scale (SUS) evaluation method is used to assess the level of user experience with the JConnect Mobile app, and Heuristic Evaluation (HE) is employed to identify more detailed usability issues within the user interface. The results of the SUS testing indicate that the level of user experience with the JConnect Mobile app is relatively low, with an average SUS score of 51.67. This falls within the "LOW" category of acceptability range. Through the Heuristic Evaluation method, a total of 16 issues were identified by all evaluators. After identifying these issues, a redesign was carried out based on the recommendations and suggestions from the evaluators. The results of the redesign testing show a significant improvement, with an average SUS score of 79.5, categorizing it as "Acceptable" within the acceptability range. This demonstrates that the design improvements have been beneficial and successful, as there has been an increase in the System Usability Scale (SUS) score after the improvements compared to the initial design.